Growing crops under organic system - Kumar, Dinesh (Indian Farming, 2015)
Organic production systems largely excludes the use of synthetic chemicals and fertilizers. It seems to be a sustainable system because it enlivens the soil, strengthens the natural resource base and sustains biological production. The area and value of organic crops is increasing year after year in India.The Government of India has also started showing concerns for promoting the organic farming in India. A good sum of money is being received in India by exporting organic products. Further, the growing export market can be tapped by the prospective farmers by growing organic crops. Under organic production systems the management of crops is quite different than the conventional ones. Special attention is required to increase the productivity of organic systems. Practices like adoption of suitable crop rotations, efficient nutrient management through organic sources of nutrients and biofertilizers, timely management of insect-pests, diseases and weeds using botanicals/ biopesticides and cultural practices need to be followed to get maximum economic yields and returns.